A Cyclic Voltammetric Study of the Redox Reaction of Cu(II) in Presence of Ascorbic Acid in Different pH Media - Haque, Farhana; Rahman, MS; Ahmed, Etmina; Bakshi, PK; Shaikh, AA (Dhaka University Journal of Science, 2013)
The electrochemical redox behavior of Cu(II), and Cu(II) in presence of ascorbic acid has been investigated at glassy carbon electrode (GCE) in aqueous phosphate buffer solution (PBS) at various pH. In the studied pH range the voltammogram consists of a cathodic and an anodic peak. Cu(II) follows one step two-electron transfer electrochemical redox reaction. The intensities of both cathodic and anodic peak current increase with increasing scan rate that are consistent with Randles-Sevcik equation. The linear behavior of peak current with the square root of scan rate indicates that the electrochemical processes are diffusion controlled. In presence of ascorbic acid both of the cathodic and anodic peak current of Cu(II) is reduced and peak positions are shifted compared to those of Cu(II) alone. These observation suggest that Cu(II) undergoes a strong interaction with ascorbic acid in the studied medium. DOI: http://dx.doi.org/10.3329/dujs.v61i2.17064 Dhaka Univ. J. Sci. 61(2): 161-166, 2013 (July)